Cow-related factors associated with intramammary infections during the 1st week postpartum in primiparous dairy cows in certified organic herds. (April 2022) - Fernandes, L.; Celestino, M.L.; Menta, P.R.; Silva, T.H.; Paiva, D.; Ribeiro, T.L.; Caixeta, L.S.; Noyes, N.R.; Machado, V.S.
Abstract: The objectives if this exploratory study were to identify variables associated with intramammary infections (IMI) during the 1st week of lactation in primiparous organic dairy cows, and to evaluate the association of those variables with somatic cell count (SCC) linear scores and milk yield in early lactation. Nulliparous cows ( n  = 240) were evaluated for: udder edema, teat edema, milk leakage (ML) and udder hygiene at weeks 6, 4, 2, and 1 prepartum and 1st week postpartum; body condition score (BCS) at 6 weeks prepartum and 1st week postpartum; age at calving (days), gestation length, dystocia, stillbirth, calf sex were included in the analysis. Milk samples from the 1st week postpartum were cultured using standard laboratory techniques and bacterial growth was considered IMI. Intramammary infection was observed in 58.7% of cows, with Staphylococcus chromogenes and S. aureus being the most prevalent pathogens. Cows with ML at 1st week postpartum were at 3.42 greater odds of IMI ( P  < 0.01). Cows with prepartum BCS ≥ 3.75 were at 3.12 greater odds of IMI ( P  < 0.01). Cows with ML in the 1st week of lactation had increased SCC ( P  < 0.01) and lower milk production in the second month of lactation ( P  = 0.05). Intervention studies are needed to evaluate if monitoring prepartum BCS and ML at early postpartum can aid in the control of IMIs in heifers in organic dairies. Highlights: Milk leakage was associated with intramammary infection. High body condition score was associated with intramammary infection. Milk leakage was associated with greater somatic cell count linear scores. Milk leakage was associated with lower milk production. Further research is needed to investigate the importance of udder edema.